1998
DOI: 10.1159/000016443
|View full text |Cite
|
Sign up to set email alerts
|

Human Enamel as a Substrate for in Vitro Acid Dissolution Studies: Influence of Tooth Surface and Morphology

Abstract: The variation in susceptibility of enamel to acid dissolution has been quantitatively assessed in vitro by examination of different surfaces of both maxillary and mandibular teeth of different morphology obtained from a pool of sound human teeth. The lingual/palatal surfaces of all teeth showed greater susceptibility to acid dissolution than the corresponding labial/buccal surfaces. The palatal surface of the maxillary teeth appeared more susceptible to acid than the lingual surface of the corresponding teeth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…Thus it can be concluded that only sound enamel (not previously damaged) had been used. Regarding mineral loss and lesion depth, a comparable trend (tables 1, 2) could be observed in all panelists, suggesting that the origin of samples did not have any considerable influence [Tucker et al, 1998]. However, the extent of incipient (early) caries developed in this in situ study varied extremely.…”
Section: Discussionsupporting
confidence: 63%
“…Thus it can be concluded that only sound enamel (not previously damaged) had been used. Regarding mineral loss and lesion depth, a comparable trend (tables 1, 2) could be observed in all panelists, suggesting that the origin of samples did not have any considerable influence [Tucker et al, 1998]. However, the extent of incipient (early) caries developed in this in situ study varied extremely.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, it was noted that some of the test subjects did not show a continuous decrease in enamel wear within the 60-min remineralization period. This finding might be explained by discrepancies between specimens prepared from various teeth, which account for the different susceptibility of specimens to erosion and abrasion [Davis and Winter, 1980;Attin et al, 1997;Tucker et al, 1998]. Moreover, in the present study, salivary pellicles were allowed to form on the surfaces of the specimens in the intervals (of at least 4 h) between the erosion/brushing steps.…”
Section: Resultsmentioning
confidence: 81%
“…Mineral loss from the tooth surface including calcium release was found to increase in association with increased acid challenge time 12,13,30,32) . However, Ca decreased after 6 cycles in both groups.…”
Section: Discussionmentioning
confidence: 96%
“…Many laboratory studies on dental erosion have focused on the chemical aspects of the erosive potential of acidic foods and beverages. In those erosion related studies, polished enamel samples were used to reduce the possible influence of superficial variations such as high fluoride content that may influence remineralization and demineralization cycles, and different ion concentrations 13,14) . Carvalho and Lussi published results on the susceptibility of dental enamel to erosive dissolution in relation to different types and surfaces of teeth, as well as the enamel depth by using polished enamel samples.…”
Section: Introductionmentioning
confidence: 99%